Women and the public space in Muslim majority countries and the West - Uthman, Ibrahim Olatunde (Universiti Kebangsaan Malaysia, 2022)
The increasing visibility of Muslim women in the public space in the Muslim majority countries and the West has led to incidences of religious condemnation and even, in some cases, violence against these women. Many fatāwā (Islamic legal verdicts) have been issued against some of these women, which have contributed to various acts of violence. Many Islamic scholars have been blamed for creating the fertile grounds for religious fanaticism, and espousing violence against women. This has brought to the front burner the feminist activism of these women in both Muslim majority countries and the West as they contest the outcry and violence against their female agency and sexual orientation, hence, the need for this study. It aims at the interrogation of the role of five women in Muslim majority countries and the West in resisting the religious opposition and violence against them. Secondary data drawn from extant literature, interviews and internet sources is used to interrogate the discourse of the purposively selected women in the context of their resistance against the opposition to their agency and choices. It adopts the intersectional and colonial/postcolonial theories to analyse the arguments of the women within the complex contexts of modernity and feminisms as illustrated by the women’s lives in contemporary societies. Whereas the women under study make no claims to any Islamic piety movements and in fact, mostly reject them; their feminist activism can still resonate with women in Islamic piety movements' opposition to the gender arrangements supervised by the religious authorities. The study, thus, encourages us to see how both Islamic scholars and Muslim feminists can unite in their deprecation of the use of Islam in supporting the perpetuation of Muslim women’s subjugation and, thereby, call for a synergy between Muslim feminists and Islamic authorities in addressing the legitimate feminist concerns among women.